2019
DOI: 10.1039/c9nr01857c
|View full text |Cite
|
Sign up to set email alerts
|

The radiation chemistry of focused electron-beam induced etching of copper in liquids

Abstract: Well-controlled, focused electron-beam induced etching of copper thin films has been successfully conducted on bulk substrates in an environmental scanning electron microscope by controlling liquid-film thickness with an in situ correlative interferometry system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 75 publications
1
9
0
Order By: Relevance
“…The deposit will build up by nucleation and growth of copper atoms and clusters. Detailed analysis of the reactions to deposit copper from aqueous copper solutions and, electron beam spatial energy deposition in the liquid in vicinity of water vapor using Monte Carlo simulations are presented in [29] and [30] respectively. Moreover, in Figure 4 it is shown that a pattern of 200 nm pitch nested lines deposited at a relatively high dose of 20 µC/cm, are merged with a flat top surface.…”
Section: Depositionmentioning
confidence: 99%
See 3 more Smart Citations
“…The deposit will build up by nucleation and growth of copper atoms and clusters. Detailed analysis of the reactions to deposit copper from aqueous copper solutions and, electron beam spatial energy deposition in the liquid in vicinity of water vapor using Monte Carlo simulations are presented in [29] and [30] respectively. Moreover, in Figure 4 it is shown that a pattern of 200 nm pitch nested lines deposited at a relatively high dose of 20 µC/cm, are merged with a flat top surface.…”
Section: Depositionmentioning
confidence: 99%
“…The deposit will build up by nucleation and growth of copper atoms and clusters. Detailed analysis of the reactions to deposit copper from aqueous copper solutions and, electron beam spatial energy deposition in the liquid in vicinity of water vapor using Monte Carlo simulations are presented in [29] and [30] respectively.…”
Section: Depositionmentioning
confidence: 99%
See 2 more Smart Citations
“…With regard to etching, the earliest study reported liquidphase focused electron beam induced etching (LP-FEBIE) of silicon nitride windows of a closed liquid cell using 1 wt% KOH (aq) [6,21]. In more recent work, copper etching on bulk substrates with no liquid cell was achieved using aqueous sulfuric acid as a liquid reactant [22,23]. The process demonstrated excellent selectivity and no damage to the underlying layers.…”
Section: Introductionmentioning
confidence: 99%